Communication Psychology Training on Safe WhatsApp Usage for Santri UMKM at Islamic Boarding Schools - Puput Mulyono; Singgih Purnomo (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
WhatsApp is one of the most widely used messaging platforms, offering fast and simple communication. Among its active users are students from Islamic boarding schools (santri), including those involved in micro, small, and medium enterprises (MSMEs). However, despite its convenience, many users lack awareness regarding digital safety and privacy, exposing them to cyber risks such as phishing, scams, and identity theft. In Nusukan, Surakarta, this issue is particularly relevant for santri who rely on WhatsApp for both academic and business communication. This community service initiative was conducted at Al-Mukminun Islamic Boarding School in Nusukan, Surakarta, with the aim of increasing awareness and understanding of safe WhatsApp usage among MSME santri. The program consisted of counseling sessions, which included lectures and interactive discussions tailored to the participants’ needs. Key topics included how to adjust privacy settings, identify suspicious links and messages, protect personal data, and recognize common cyber threats. Participants responded positively to the training. Feedback showed that 80% of them reported they would avoid clicking unknown links in messages. Another 80% stated they would refrain from sharing personal information with strangers. Furthermore, 80% expressed their commitment to regularly updating the WhatsApp application to ensure optimal security features are in place. This program successfully raised awareness and empowered santri with essential knowledge about digital communication safety. It highlights the importance of integrating communication psychology and practical digital literacy into community education to support secure online behavior for young entrepreneurs. Overall, this training shows that a contextual and applicable communication psychology approach is very effective in forming positive digital awareness and behavior in religious-based communities such as MSME students.